The immunization status and drop out of 0-3 years children in a rural area of Jaipur, Rajasthan, India - Ahluwalia, Sumit; Mandarwal, Dharmendra (International Journal of Research in Medical Sciences, 2020)
Background: The vaccine preventable diseases are one of the causes of morbidity and mortality among children despite implementation of immunization program. Methods: A cross-sectional study was conducted in rural area of Jaipur to know immunization status of 0-3 years of children and its relation to socio-demographic factors and reason for dropout. Results: Total no of families in study was 194. Majority of them were Hindu ( 94.84%). Majority of children belong to socioeconomic class V (55.%) and socioeconomic class IV (28.5%). 48.17% mothers were of 25-29 years of age group. 93.02%of mothers were housewives. Majority of mothers (42.5%) were illiterate, BCG vaccination coverage was found to be 71.09%, while that of OPV was 71.09%, DPT 64.96%, Measles 60.71%, and MMR vaccination was 3.43%. This study shows that drop our rate for DPT was 19.4%, dropout rate of OPV was 22.33%. Left out rate for DPT was 35.03%. Conclusions: Majority of children who were non immunized belong to illiterate mothers. Reasons for non-immunization in maximum number of cases was lack of information, wrong ideas regarding immunization and unaware of need for immunization.